Enterprise Architectural Design Using Model The Open Group Architecture Framework (TOGAF) ADM for IS Strategy Planning (Case Study : Modern Islamic Boarding School Zamzam Muhammadiyah Cilongok, Banyumas Regency) - Shalsabila Maulidya Paramitha; Irfan Nurfaizin; Elvandra Desmerio R (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
In improving services in the field of education supported by increasingly rapid technological developments, PPM ZamZam Muhammadiyah Cilongok must be able to harmonize business strategies with information technology, where the use of information technology, especially in the Human Resources (HR) function, is still not integrated with each other. maximum said. In planning the IS/IT strategy of an architectural firm (EA) in order to achieve alignment of the IS/IT strategy with the business strategy of the organization. EA is seen as a logistical, comprehensive, and holistic approach to defining, designing, and implementing systems and components simultaneously. The current condition of Ponpes Zam-zam does not yet have a specific and integrated school architecture information system in accordance with the needs and objectives of Ponpes Zam-zam, which collaborates to jointly develop the Registration System, Finance and Information Technology-based Pondok learning system. The Open Group Architecture Framework (TOGAF) is a framework that provides methods and tools for building, managing and implementing, and maintaining enterprise architectures. The stages used in this architectural design are Preparation, Architectural Vision, Business Architecture, Information Systems Architecture, Technology Architecture. The design of the Islamic Boarding School Information System is carried out using the main business process approach and existing supporting business processes. The expected result of this research is a proposed TOGAF model that is adapted to the Ponpes business processes and needs in designing enterprise architecture for IS/IT strategic planning